Employment protection and labour productivity growth in the EU: Skill-specific effects during and after the Great Recession - Igor Fedotenkov; Virmantas Kvedaras; Miguel Sanchez-Martinez (European Commission, 2022)
The paper investigates the relationship between employment protection legislation (EPL hereafter) and labour productivity growth in the EU in the context of the Great Recession. We consider the crisis and recovery periods, evaluate the relevance of both levels and changes in EPL for productivity growth, establish the presence of some nonlinearities, and explore the conditioning role played by the skills of the labour force, captured by different levels of education. We find that stricter labour protection reduces labour productivity growth in sectors with a large share of workers with tertiary education, whereas this effect is negligible or positive in sectors where workers with secondary or only primary education are more prevalent, respectively. We establish that overly strict regulation is more harmful, whereas its moderate level can be even beneficial in regular (non-crisis) times. In the long run, we document that an increase in EPL stimulates employers to substitute labour with capital, partially mitigating the overall negative effect on labour productivity growth. We provide several hypotheses that could explain our findings and discuss potential policy implications supported by a back-of-the-envelope calculation.
Keywords: E24; I25; J24; J88; 330; Labour productivity; employment protection legislation; skills; education; Great Recession